2008
DOI: 10.1111/j.1365-2818.2008.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled microaspiration for high‐pressure freezing: a new method for ultrastructural preservation of fragile and sparse tissues for TEM and electron tomography

Abstract: SummaryHigh-pressure freezing is the preferred method to prepare thick biological specimens for ultrastructural studies. However, the advantages obtained by this method often prove unattainable for samples that are difficult to handle during the freezing and substitution protocols. Delicate and sparse samples are difficult to manipulate and maintain intact throughout the sequence of freezing, infiltration, embedding and final orientation for sectioning and subsequent transmission electron microscopy. An establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…4B). Note that owing to the specific sample preparation method chosen for the 2D TEM imaging, internal membranes showed low contrast (Giddings, 2003;McDonald and Morphew, 1993;Triffo et al, 2008). Also, owing to the difference in heavy metal staining needed to image samples with FIB-SEM, the texture of the chromatin within the nucleus appeared to be less heterogeneous in comparison to that upon staining for TEM (Fig.…”
Section: Membrane Protrusions In the Intercellular Space Form An Extementioning
confidence: 99%
See 1 more Smart Citation
“…4B). Note that owing to the specific sample preparation method chosen for the 2D TEM imaging, internal membranes showed low contrast (Giddings, 2003;McDonald and Morphew, 1993;Triffo et al, 2008). Also, owing to the difference in heavy metal staining needed to image samples with FIB-SEM, the texture of the chromatin within the nucleus appeared to be less heterogeneous in comparison to that upon staining for TEM (Fig.…”
Section: Membrane Protrusions In the Intercellular Space Form An Extementioning
confidence: 99%
“…2). The cellular ultrastructure showed exquisite preservation owing to the ultra-rapid freezing and the freeze-substitution process (McDonald and Auer, 2006;Triffo et al, 2008), otherwise known as high-pressure freezing with freeze substitution (HPF-FS). The compact spacing of elements within the cytoplasm ( Fig.…”
Section: Hmt-3522-s1 Cells In Biomimetic 3d Tissue Culture Show Growtmentioning
confidence: 99%
“…However, fresh tissue microdissection and the exposure of unfixed tissues to relatively high levels of cryoprotectants (e.g. 20% glycerol), just prior to high-pressure freezing, can lead to physical damage or osmotic stress (Triffo et al, 2008). To avoid aggregation artifacts caused by the dehydration step in conventional protocols, yet guard against osmotic stress in fresh dissected tissue sample upon exposure to cryoprotectants, we adopted a conservative approach to sample preparation.…”
Section: Fixation Strategy For Ultrastructural Analysismentioning
confidence: 99%
“…Using the Leica automated freeze-substitution system AFS (Leica Microsystems, Vienna, Austria), cryofixed specimens were freeze-substituted in anhydrous acetone containing 1% osmium tetroxide and 0.1% uranyl acetate and after several rinses in pure acetone infiltrated with Epon-Araldite following established protocols (McDonald and Müller-Reichert, 2002;McDonald, 2007;Triffo et al, 2008). Specimens were flat-embedded between two microscopy slides and polymerized at 60˚C over 1 to 2 days.…”
Section: Freeze Substitutionmentioning
confidence: 99%
“…Sosinsky et al [87] showed that chemical pre-fixation before HPF and FS followed by resin embedding provided a better preservation of ultrastructure than a single chemical fixation. However, exposure of fresh, microdissected tissue to highly concentrated cryo-protectants can lead to osmotic stress and physical damage [126]. Using aldehyde fixation before HPF-FS and resin embedding, Ewald et al [127] achieved high-quality ultrastructural preservation of cell membranes in multilayered epithelium.…”
Section: At the Edge Of Possibilities -Hybrid Techniquesmentioning
confidence: 99%